The Comparison of outcomes between USG guided ESWL Vs Fluoroscopy guided ESWL – Our institutional Experience - Pugazhenthi Periasamy; Jayaprakash Narashimman; Rajasekar Maruthamuthu; Rajkumar Ramakrishnan; Kuladeep Vankadara (Asian Journal of Medical Sciences, 2024)
Background: Extracorporeal shockwave lithotripsy (ESWL) is a commonly used non-invasive treatment modality for urolithiasis. While fluoroscopy (FS)-guided ESWL has been the traditional approach, the use of ultrasound (USG) guidance has gained traction due to its potential benefits in terms of reduced radiation exposure and improved stone targeting. Aims and Objectives: The aims and objectives are to study the safety and efficacy of extracorporeal shock wave lithotripsy in the management of renal stones, outcomes of overall stone-free rate (SFR), pain intensity, urinary biochemical variables, mean hospital stay, quality of life, and adverse events. Materials and Methods: Patient data from the period of May 2022 to April 2023 were reviewed, including 20 patients who underwent USG-guided ESWL and 20 patients who underwent FS-guided ESWL. Results: Our analysis revealed that the USG-guided ESWL group demonstrated comparable stone fragmentation rates and SFR (P-value) when compared to the FS-guided group. Moreover, radiation exposure was significantly reduced in the USG-guided ESWL group, with a mean total FS time of [55] s compared to [3005] s in the FS-guided group. No significant differences were observed in terms of complications between the two groups. Conclusion: This study highlights the successful implementation of USG-guided ESWL in our institution’s experience, showing comparable outcomes in terms of stone fragmentation rates and SFR, while significantly reducing radiation exposure, also can be considered an effective and safe alternative for the treatment of urolithiasis.